The Concept and Criteria of Sakata ‘Anhu in the Kitab Sunan Abu Dawud - Akbar, Muhammad; Febriyeni, Febriyeni (El-Rusyd, 2026)
Sunan Abu Dawud are hadiths that Imam Abu Dawud did not comment on in his Sunan. Imam Abu Dawud's silence on these hadiths has given rise to differing opinions among scholars regarding their quality and validity. Some scholars believe these hadiths can be used as evidence because they are considered hadiths. valid, while others believe that further research is needed into the quality of the sanad and its mater. Therefore, this study aims to examine the concept of Sakata'anhu, analyzing the quality of these hadiths through the critical sanad and matan approaches, and comparing Imam Abu Dawud's assessments with those of classical and contemporary hadith scholars. This research uses a qualitative method. Primary data were obtained from the Sunan Abu Dawud book. The Message of Abi Dawud to the People of Makkah, kitab of rijal al-hadith, books of sharh, and works of takhrij related to hadiths. Secondary data comes from books on hadith, scientific journals, theses, and other supporting literature. The methods used include hadith interpretation, sanad (translation of the narrators), analysis of the credibility of narrators through the study of jarh wa ta'dil (translation of the narrators), sanad criticism, matan criticism, and comparative analysis of the assessments of hadith scholars. The results of the study indicate that the hadiths Sakata'anhu in Sunan Abu Dawud have varying qualities, ranging from sahih to hasan, to hadiths that are disputed due to weaknesses in some of the narrators. In terms of sanad, most of the hadiths studied have a continuous sanad (defense al-sanad) and are supported by other transmission lines that can strengthen their position. Meanwhile, from the perspective of the text, no irregularities were found (syudzudz) or hidden defects (god) that affect the substance of the hadith. The content of these hadiths also does not contradict the Quran, stronger hadiths, common sense, or historical facts.